The Effect of Bariatric Surgery versus Intensive Medical Care on Prevention of Microalbuminuria in Patients with Type 2 Diabetes: 3 Year Experience of a Prospective Study - Soliman, Amin; Soliman, Haythum; Naguib, Mervat (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Bariatric surgery could improve diabetic kidney disease; however, the effect of surgery versus medical therapy on renal out comes needs further evaluation. AIM: The aim of the study was to investigate the effect of sleeve-gastrectomy versus intensive medical therapy on the prevention of albuminuria in patients with Type 2 diabetes mellitus (T2DM). METHODS: This is a prospective study of 33 patients with T2DM undergoing sleeve gastrectomy matched for age, sex, and duration of diabetes to 64 medically treated patients. Urinary albumin/creatinine ratio (uACR) was assessed before and 3–year after intervention. RESULTS: At baseline, there was no significant difference between surgical and medical group regarding body mass index (BMI), blood pressure, Hemoglobin A1c (HbA1c), or uACR. After 3 years of interventions the mean BMI (kg/m2) and HbA1c (%) became significantly lower in the surgical group compared to medical group. Although mean uACR (g/mg) increased after interventions compared to its levels before interventions in both surgical (11.7 ± 4.8 vs.18.2 ± 5.9) g/mg and medical (13.4 ± 4.5 vs.17.1 ± 6) g/mg groups, albuminuria developed in only three surgical patients and two medical patients (p > 0.05). CONCLUSION: Although bariatric surgery is associated with more reduction in body weight and better glycemic control than intensive medical therapy, sleeve-gastrectomy may not be superior to intensive medical care in prevention of microalbuminuria in patients with T2DM.